PENGARUH PROFITABILITAS, FIRM SIZE, RISIKO BISNIS, ASSET GROWTH, LEVERAGE, KEBIJAKAN DIVIDEN TERHADAP INSTITUTIONAL OWNERSHIP (Perusahaan Property & Real Estate yang terdaftar di Bursa Efek Indonesia Tahun 2011 – 2014) - Nardi Sunardi; Sarwani . (Inovasi, 2015)
INFLUENCES OF PROFITABILITY, FIRM SIZE, BUSSINES RISK, ASSET GROWTH, LEVERAGE, DIVIDEND POLICYTO INSTITUTIONAL OWNERSHIP(Property & Real Estate Company Listed on the Indonesia Stock Exchange Year 2011-2014). The aims of this research is to examine the effect of propitability, firm size, bussines risk,  asset growth, leverage, dividen policy as the independen variable and institutional ownership as the dependen variable (studyat Real Estate and Property Company Lisyting in Indonesian Stock Exchange since 2011 until 2014). The population in this study are 23 Real Estate and Property companies listed on the Indonesian Stock Exchange from 2011 until 2014. The sample in this study is Real Estate and Property company according to the criteria established.  Regression analysis was performed with based on the results of data panel analysis this study concludes some of the following: (1) Variable propitability proven to negative and significan the institutional ownership, (2) Variable firm size proven to negative and significan the institutional ownership,  (3) Variable business risk proven to negative and significan the institutional ownership, (4) Variable asset growth proven to positive  and significan the institutional ownership, (5) Variable leverage proven to positive and significan the institutional ownership,  (6) Variable dividend policy proven to negative and significan the institutional ownership, Key words: propitability, firm size, bussines risk, asset growth, leverage, Dividen policy, insitutisional ownership.